Memorial de Maria Moura: uma obra residual do medievo - Barros, Thaís Ferreira (2024)
The novel Memorial de Maria Moura (1992), written by Rachel de Queiroz (1910-2003), from Ceará, has an immeasurable value for northeastern culture and its themes are composed of cangaço, coronelismo, matriarchalism, jaguncismo, popular beliefs, beatism and large sugarcane farms. These elements are full of medieval residues because they were brought by Europeans and adapted to our tropical reality during the colonization process of the Brazilian Northeast. From this perspective, the central objective of this search was to prove and examine the medieval substrates present in Memorial de Maria Moura, identifying and examining in the work the sediments with mental, imaginary, cultural, religious, ethnic, physical and structural aspects. The investigation is developed through comparative analysis, of an interdisciplinary nature, between the aforementioned residues identified in the literary work and other areas of knowledge such as History, Sociology, Anthropology, among other areas. We use as a theoretical reference the Theory of Literary and Cultural Residuality, which was systematized by professor, poet critic and essayist Roberto Pontes. This Theory is composed of operators called mentality, imaginary, cultural hybridity, endoculturation and crystallization. These operators follow the basic conception of residue proposed by the systematizer who says the following: “In culture and literature there is nothing original; everything is remnant; therefore, everything is residual.” (PONTES, 2020, p. 33). Regarding the works that supported this search by means of the dialogue with the aforementioned theory, it is also worth highlighting studies by authors linked to other theoretical orientations, such as BASCHET (2006), BLOCH (1987), CARVALHAL (1986), DUBY (1980), FRANCO JÚNIOR (1988), FREYRE (2003), PRADO JÚNIOR (2011), SOUZA (1986) and VASSALLO (1993). As a conclusion of this research, we emphasize the preservation pf medieval elements in the rural context described by Rachel de Queiros. This can be observed, for example, in relation to the imaginary that was formed and propagated in the imagination of the characters in the narrative.